Implementation of Achieve Coaching Model in Learning Arabic Li Ghayr Natiqina Biha - Djamilah, Wulan Indah Fatimatul; Walidin, Muhammad (Raudhah Publisher, 2024)
This paper aims to describe learning Arabic based on the ACHIEVE coaching model. The research approach is descriptive qualitative. The type of research is library research. The results from searching data of this library research describe how the patterns of learning Arabic using the ACIEVE coaching model are. The ACHIEVE coaching model has been used successfully for professionals, and the author tries to create it to be adopted in Arabic learning. This ACHIEVE Coaching Model will give a student (as a coachee) to find a strategy from himself that he finds himself and is the most appropriate solution for him in order to face the challenges / problems faced in his learning activities, thus helping the student achieve learning goals to the fullest. Thus, the learning outcomes obtained will increase and be optimal.